Positive HABITATS for physical activity: Examining use of parks and its contribution to physical activity levels in mid-to older-aged adults. (May 2020) - Hooper, Paula; Foster, Sarah; Edwards, Nicole; Turrell, Gavin; Burton, Nicola; Giles-Corti, Billie; Brown, Wendy J.
Abstract: Studies of parks and physical activity rarely identify the actual spaces participants use. Using data from the HABITAT project, a longitudinal cohort of mid-to older-aged (40–70 years) respondents (n = 11, 036) living in Brisbane Australia, this study examined (1) the demographic characteristics of users and non-users of parks; (2) the park used and the characteristics and features of the most popular reported spaces; and (3) the level of physical activity undertaken in the reported parks and whether users had higher total physical activity levels than non-users. Park use was significantly higher (p < 0.01) among dog walkers, couples (over 40) living with children, and those living in least disadvantaged areas. Regular park use was significantly higher among users of larger-sized neighbourhood and district-catchment parks. Park users were 35% more likely to meet the physical activity guidelines (OR = 1.35, 95%CI 1.21–1.50, p < 0.001) compared with those who indicated they did nto regularly use a park. The size of the park used was positively associated with participation in physical activity. Users of larger-sized parks spent more time doing vigorous activity and engaged in more activity sessions than non-users. Future data obtained from large populations, including spatial examination of the actual parks used and their characteristics, are essential to facilitate planning for park provision, optimising the use of these spaces for recreation and physical activity by mid-to older-aged adults, and creating healthy communities. Highlights: Studies of public open space (POS) and physical activity rarely identify the actual spaces participants use. Planning for POS has followed a standards-based approach built on longstanding assumptions of use. This study identified the public open spaces used and the level of physical activity undertaken in the spaces. Regular POS users were 35% more likely to meet the Active Australia physical activity guidelines. Users of larger-sized POS spent more time doing vigorous activity and engaged in more activity sessions than non-users.